(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
Patients in the operating room have a very high risk of falling, because the patient is not fully conscious so they can fall to the floor unintentionally. The impact of the risk of falling can be detrimental to patients, one of which is physical injury and can even result in death. Lack of knowledge of nurses in preventing the risk of falling is one of the causes. This study aims to determine whether there is a relationship between the level of knowledge of nurses in the operating room and the prevention of the risk of falling in patients. The design of this study used a cross-sectional study with a total sampling technique with a sample size of 30 people. The results of the Spearman test showed that there was a relationship between knowledge and the prevention of the risk of falling p-value = 0.023 with a significance limit (α <0.05). The conclusion of this study is that there is a relationship between nurses’ knowledge and the prevention of the risk of falling in patients.